Analisa Penerapan Standar Gri 400 Pada Sustainability Report Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (Bei) Tahun 2024 - Nanda Ismail Hasan; Rika Gunawan; Ocha Widya Sari; Zul Azmi (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze sustainability reporting practices and the level of adoption and disclosure of the Global Reporting Initiative (GRI) 400 social aspects in companies listed on the Indonesia Stock Exchange (IDX) in 2024. The study uses a quantitative descriptive approach with a content analysis method on the Sustainability Reports of companies in 11 sectors on the IDX. Of the 955 companies listed on the IDX, 847 companies have published Sustainability Reports, but only 296 companies have explicitly adopted the GRI Standards. The results show that sustainability reporting practices in Indonesia have developed in terms of quantity, but the adoption of international reporting standards is still limited and varies across sectors. Disclosure of the GRI 400 social aspects tends to focus on internal company indicators, especially occupational health and safety, personnel, and training and education, while indicators related to human rights, indigenous peoples, public policy, and supply chains are still relatively low. These findings indicate that the implementation of GRI 400 in Indonesia is still partial and compliance-oriented, so that it is necessary to strengthen regulations and increase company commitment to encourage more comprehensive disclosure of social aspects.